Comparison of calibrated dilute thrombin time and aPTT tests with LC-MS/MS for the therapeutic monitoring of patients treated with dabigatran etexilate - Douxfils, Jonathan; Dogné, Jean-Michel; Mullier, François; Chatelain, Bernard; Rönquist-Nii, Yuko; Malmström, Rickard E.; Hjemdahl, Paul (Thrombosis and Haemostasis, 2013)
Ways to monitor dabigatran etexilate (DE) therapy would be useful in certain situations. Functional assays such as aPTT or Hemoclot® Thrombin Inhibitor (HTI) have been proposed to evaluate dabigatran concentrations, but previous findings are based on in vitro studies and results must be confirmed in clinical samples. The aim of this study was to compare aPTT and HTI measurements with liquid chromatography- tandem mass spectrometry (LC-MS/MS) measurements of dabigatran in plasma samples from DE treated patients. Seventy-one plasma samples were included. aPTT was performed using STA-CKPrest® and SynthASil®. HTI was performed according to instructions from the manufacturer. The LC-MS/MS method utilised dabigatran- d3 as internal standard. The plasma concentration range was 0 to 645 ng/ml as measured by LC-MS/MS. Overall, the HTI and LC-MS/ MS analyses correlated well (r2=0.97). The Bland-Altman analysis showed a mean difference of 9 ng/ml (SD: 20 ng/ml). However, the HTI performed poorly at concentrations <50 ng/ml. LC-MS/MS was sensitive (limit of quantification 1.1 ng/ml) and specific for dabigatran. The aPTT methods did not correlate well with plasma concentrations measured by LC-MS/MS (r2 = 0.59 with SynthASil® and 0.50 with STACKPrest ®). In conclusion, the poor sensitivity, the important inter-individual variability, and the poor correlation with LC-MS/MS preclude the use of aPTT to estimate dabigatran concentrations. Due to its small inter-individual variability and good agreement with LC-MS/MS measurements, we recommend the use of HTI assays to rather accurately estimate concentrations of dabigatran <50 ng/ml. Quantification of lower dabigatran levels in DE-treated patients requires the “reference” LC-MS/MS method.
Keywords: Dabigatran; coagulation assay; LC-MS/MS; monitoring; aPTT